Selection of Hormonal Reference Values for Undescended Testicle Case in 8-Year-Old Boy with Abnormal Chromosome - Corry, Vina; Pasaribu, Merci M. (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Establishing the diagnosis of undescended testicles requires appropriate hormonal laboratory reference values basedon age and gender. An 8-year-old boy with an undescended testicle, mental retardation, and stunting had a blood test thatwas carried out at the Clinical Pathology Laboratory, dr. Cipto Mangunkusumo (RSCM) Hospital on February 6, 2020, withtestosterone levels of 0.69 nmol/L (N male: 4.94-32.01 nmol/L) indicating decreased testosterone levels. The patient wasconsulted from urological surgery to pediatric endocrinology to determine the presence or rudiment of the patient'stesticles. Using the reference range of testosterone values assists clinicians in determining the diagnosis, monitoringtherapy, and prognosis of a disease. There are some testosterone reference values, which are currently available, includingCanadian Laboratory Initiative on Pediatric Reference Intervals Database (CALIPER) and the Tanner stage reference value.Later is more applicable because it is based on chronological age and secondary sexual development in assessing pubertydevelopment. A case of an 8-year-old boy with a clinical diagnosis of an undescended testicle, the laboratory test resultsshowed normal-low testosterone levels using the CALIPER and Tanner stage ranges according to the patient's age. Noincrease of testosterone levels after the second HCG stimulation test might be due to differences in the HCG administrationprotocol; therefore, the diagnosis of anorchia had not been established, and chromosome abnormalities of 46 XY, +6 Mar,17 dmin on chromosome analysis suggested the suspected syndrome. These findings were consistent with the suspicion ofprimary hypogonadism in children with suspected syndrome caused by bilateral cryptorchidism with a suspectedseminiferous tubular defect.